Integrating Canva Audiovisual Media into Classroom Management: Exploration of Perceptions from Teachers and Students - Nurlinda Nurlinda; Nurdin Noni; Abdullah Abdullah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Speaking is an essential component of English language learning, yet many EFL (English as a Foreign Language) students continue to struggle with fluency, confidence, and engagement in speaking activities. The integration of digital learning media is increasingly seen as a potential solution to these challenges, particularly through the use of audiovisual platforms such as Canva. This study aims to explore the perceptions of English language teachers and students regarding the use of Canva-based audiovisual media in improving students’ English speaking skills and supporting effective classroom management. Conducted at Pondok Pesantren Putra IMMIM Makassar, this qualitative study involved one English teacher and ten eighth-grade students. Data were collected through semi-structured interviews and classroom observations. The findings showed that teachers perceived Canva as a practical and innovative tool that supports structured lesson planning, increases student engagement, and aligns with 21st-century educational goals. Canva’s visual and audio features help improve focus, minimize distractions, and deliver content more effectively. Meanwhile, students gave positive perceptions, stating that Canva made speaking lessons more enjoyable, improved their understanding of the material, and increased their confidence in speaking. Although some technical limitations were noted, both teachers and students agreed that Canva significantly improved the overall learning environment. The study concludes by recommending consistent integration of audiovisual digital media to support teaching quality and speaking proficiency in EFL classrooms.